Basic Football Skill Instruments for Indonesian Junior Players - Chandra, Ketut Chandra Adinata Kusuma; I Wayan Artanayasa; Made Agus Dharmadi (Universitas Pendidikan Ganesha, 2023)
Football skills instruments are needed by football coaches or practitioners to identify talents and evaluate the training process of each player. Currently, there are many types of football skill instruments, but instruments that are in accordance with the characteristics of Indonesian players and the Indonesian Football Development Curriculum (Filanesia) are not yet available. The purpose of this study was to analyze the development of football skills instruments that are suitable for Filanesia in order to obtain information on the needs, urgency, benefits, and draft models of these instruments. This research approach uses mixed methods, namely quantitative and qualitative. A total of 30 respondents were involved in this study, consisting of 25 football coaches and 5 expert lecturers in the field of football. Data was collected using questionnaires distributed through g-forms and through Focus Group Discussion (FGD) activities. Questionnaire results were analyzed using quantitative descriptive statistics. Apart from this analysis, data triangulation was used to analyse the result of the interviews and discussions during FGD. The results of this study indicate that a football skill instrument is very useful for coaches and players, and the urgency of developing a Filanesia-based football skill instrument model is very high. Thus, a draft instrument model has been produced for two levels of age groups (10–12 years and 13–16 years). Of course, this is an opportunity for further research, namely to validate the two draft models and measure their reliability so that the two test models can be used by football school coaches.